2018
DOI: 10.4269/ajtmh.18-0440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Surveillance of Plasmodium falciparum Drug Resistance Markers in Clinical Samples from Botswana

Abstract: Drug-resistant Plasmodium falciparum is a major threat to global malaria control and elimination efforts. In Botswana, a southern African country approaching malaria elimination, P. falciparum molecular data are not available. Parasites were assessed through pollymerase chain reaction (PCR) for confirmation of positive rapid diagnostic tests, multiplicity of infection (MOI), and drug resistance markers among isolates from clinical uncomplicated malaria cases collected at health facilities. Of 211 dried blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…More importantly, P. falciparum may be generally tolerant to lumefantrine, which is one of the compounds utilized in first line treatment together with the highly efficacious artemether. The same study found two synonymous mutations -V555V and R513R -in the propeller domain of the P. falciparum Kelch13 gene (pfk13) (Tawe et al, 2018a(Tawe et al, , 2018b which is implicated in the resistance to artemisinin. It should be noted that neither of these genetic variants were associated with a delayed parasite clearance phenotype.…”
Section: Drug Resistance Surveillancementioning
confidence: 87%
See 3 more Smart Citations
“…More importantly, P. falciparum may be generally tolerant to lumefantrine, which is one of the compounds utilized in first line treatment together with the highly efficacious artemether. The same study found two synonymous mutations -V555V and R513R -in the propeller domain of the P. falciparum Kelch13 gene (pfk13) (Tawe et al, 2018a(Tawe et al, , 2018b which is implicated in the resistance to artemisinin. It should be noted that neither of these genetic variants were associated with a delayed parasite clearance phenotype.…”
Section: Drug Resistance Surveillancementioning
confidence: 87%
“…Admixture has occurred between the two ethnic groups to various extents (Schuster et al, 2010). As a consequence, there is a wider spectrum of genotypes and phenotypes when considering genetic characteristics such as Duffy antigen, sickle cell trait, glucose-6-phosphate dehydrogenase (G6PD), and detoxifying liver enzymes (Howes et al, 2011;Motshoge et al, 2018;Tawe et al, 2018aTawe et al, , 2018b. These human genetic factors play a pivotal role in susceptibility to malaria infection and associated morbidity (Haldane, 1949;Sirugo et al, 2014), as well as for metabolism of medications currently on the market (Tawe et al, 2018a(Tawe et al, , 2018b.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular surveillance of imported malaria cases is an important public health activity that can aid in the detection of drug-resistant P. falciparum parasites [21,22]. Recent advancements in next-generation sequencing are providing a new way to rapidly detect and characterize drug-resistant malaria parasites, including minor parasite populations in mixed infection P. falciparum cases [23,24].…”
Section: Introductionmentioning
confidence: 99%